2006
DOI: 10.1007/s11255-006-6676-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological features of bladder carcinoma: Experience from a tertiary care hospital of Pakistan

Abstract: More than 90% of primary bladder carcinoma are of transitional cell variety and over 60% having muscle invasive disease at the time of diagnosis. Even in patients with superficial disease, majority (i.e. 98%) have invasion of lamina propria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Urothelial tumors were the only histological type seen in our study which was also reported (Rafique et al, 2006;Al-Bazzaz, 2009). Bladder cancer is rare in people younger than 50 years of age even though it can occur at any age.…”
Section: Discussionsupporting
confidence: 86%
“…Urothelial tumors were the only histological type seen in our study which was also reported (Rafique et al, 2006;Al-Bazzaz, 2009). Bladder cancer is rare in people younger than 50 years of age even though it can occur at any age.…”
Section: Discussionsupporting
confidence: 86%
“…As many as 50% cases of bladder cancer are attributed to smoking in men and 33% in women. 1 In our study out of 30 patients 23 (75.9%) patients were smokers. The incidence in our study of male smoker is 75.9%, which is comparable to that of 65% of bladder cancer in men is attributed to cigarette smoking.…”
mentioning
confidence: 51%
“…1 So we reached at a conclusion that factory workers (Textiles, tyre rubber and cable worker) are at high risk for CA urinary bladder in our country. A lot of other carcinogens or highrisk occupations are still to be detected apart from those present in the literature.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The average age at diagnosis of bladder cancer patients in Sri Lanka is similar to that of India which is around 65 [ 15 ]. In Pakistan the mean age of bladder cancer is around 55–58 years [ 17 , 18 ]. In the present study male to female ratio was 4.1 : 1, compared to the ratio of 3 : 1 quoted worldwide [ 3 , 21 ].…”
Section: Discussionmentioning
confidence: 99%